Etika Wanita Berpakaian Menurut Imam Nawawi (Studi Analisis Terhadap Kitab Alminhaj Syarah Shahih Muslim) - Nurafnita Dewi (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2025)
This research aims to understand the proper dress ethics for Muslim women according to Islamic teachings, the types of clothing that are forbidden, and the collection of hadiths that discuss the ethics of women's dress. This study is a library research and is classified as qualitative research using content analysis techniques. The conclusion of this study is that Muslim women are required to observe specific dress ethics: they must not wear thin or transparent clothing that reveals the body, nor wear tight clothing that outlines the shape of the body, and should also avoid extravagance in dress. Instead, they should wear loose and thick garments that protect them from undesirable consequences. The aim of this research is to guide Muslim women to dress in accordance with Islamic principles.